2013
DOI: 10.1007/s00330-013-2846-6
|View full text |Cite
|
Sign up to set email alerts
|

How far can the radiation dose be lowered in head CT with iterative reconstruction? Analysis of imaging quality and diagnostic accuracy

Abstract: • Cranial CT using iterative reconstruction provides diagnostic images with 43 % mAs reduction. • Blurring of infratentorial images becomes evident using low-radiation head CT. • Head diameter was inversely correlated with imaging quality in the infratentorium. • Lowering tube kilovoltage requires a higher radiation dose to maintain image quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…The mean of three measurements per patient was used for further analysis and sharpness quantified in terms of gradient or maximal slope (change in HU per pixel). 17,18 Qualitative image analysis Qualitative analysis of images was independently performed by two board-certified, subspecialty-certified Readers 2 and 3. Randomized and anonymous assessment of studies was ensured through random selection of subjects or reconstructions by one of the authors and their presentation to the readers in a blinded fashion.…”
Section: Dose Measurementsmentioning
confidence: 99%
“…The mean of three measurements per patient was used for further analysis and sharpness quantified in terms of gradient or maximal slope (change in HU per pixel). 17,18 Qualitative image analysis Qualitative analysis of images was independently performed by two board-certified, subspecialty-certified Readers 2 and 3. Randomized and anonymous assessment of studies was ensured through random selection of subjects or reconstructions by one of the authors and their presentation to the readers in a blinded fashion.…”
Section: Dose Measurementsmentioning
confidence: 99%
“…For this reason, we prefer exclusive adjustment of current except for paediatric applications. Preservation of diagnostic image quality has also been reported by Wu et al 18 for 36.7-and 33.6-mGy CTDI protocols and the use of a different IR algorithm. However, in that study, data were acquired by conventional detector, and the obtained CNR values were significantly lower.…”
Section: Discussionmentioning
confidence: 68%
“…21 At this point, a number of studies have assessed the benefit of IR in head CT and the published dose-saving potential varies from 20% to 40%. 7,15,18,[22][23][24][25][26] In our own experience, use of sinogram-affirmed IR may increase SNR of grey and white matter by .40% but has only a relatively small effect on image sharpness. 27 While the iterative algorithms are currently subject to constant refinement, vendors are also aiming at decreasing scannerrelated system-inherent noise by designing more noise efficient detectors.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, we employed a fixed mA technique, which was consistent at the start of the study with the 2012 recommendations by the American Association of Medical Physicists (AAPM) (33), which stated that AEC use was optional, as many sites did not elect to use AEC for head examinations. Most efforts to lower radiation dose in head CT examinations utilize subjective or objective measures of image quality rather than observer performance estimates (27, 32, 34, 35). Prior authors have found that iterative reconstruction is beneficial in improving image quality in unenhanced head CT (35).…”
Section: Discussionmentioning
confidence: 99%